Phenol degradation using glassy carbon electrodes modified with particles of Co-Mo alloy - Orozco, S.I.; Blanco Jerez, Leonor María; Garza Elizondo, Mario Alberto (2013)
This paper reports on a study aimed to modify the surface of glassy carbon (VC) with Co-Mo nanoparticles and to determine their morphology and composition in order to evaluate their electrocatalytic activity for degrading phenol. The electrochemical deposition of Co-Mo from CoSO4 and Na2MoO4 in two molar relations (Co:Mo 2.3:1 and 20:1) was analyzed. Experiments were conducted in a conventional three-electrode cell using glassy carbon as the working electrode (WE), Ag/AgCl(s) as the reference electrode (RE) and Pt as the auxiliary electrode (CE). A citrate bath at pH 6 was used as supporting electrolyte. The electrode modification was carried out potentiostatically at –1.1 V vs. Ag/AgCl(s) and galvanostatically at –0.003 A/cm2. The modified electrodes were characterized by XRD, TEM and XPS. Analyses showed that the obtained deposits were a mixture of Co2Mo3 alloy and CoMoO3 oxide. The ability of the electrode modified with Co-Mo particles to degrade phenol was studied. Degradation rate was 95% in 3 hours on a synthetic solution of phenol 30 ppm. UV-Vis spectra of the solutions obtained during electrochemical phenol reduction allowed identifying benzene and cyclohexane as the reaction products.